The tadpole of Elachistocleis helianneae Caramaschi, 2010 (Anura: Microhylidae) - Dias-Souza, Marcos Roberto; Costa-Campos, Carlos Eduardo; Menin, Marcelo (Zootaxa, 2019)
The neotropical genus Elachistocleis Parker comprises 18 described species [including Elachistocleis ovalis (Schneider) which is considered a nomen dubium by Caramaschi (2010), with pending revision]. This genus is distributed in Central America and most of South America, from Panama and Trinidad to southern Paraguay, including central Argentina, Uruguay, Venezuela, Colombia, Bolivia, Guyana, Surinam, French Guiana, and Brazil (Marinho et al. 2018; Frost 2019). Currently, the tadpoles of ten species have been described and/or figured: Elachistocleis bicolor (Guérin-Méneville), E. cesarii (Miranda-Ribeiro), E. erythrogaster Kwet and Di-Bernardo, E. haroi Pereyra, Akmentins, Laufer and Vaira, E. muiraquitan Nunes-de-Almeida and Toledo, E. ovalis, E. panamensis (Dunn, Trapido and Evans), E. pearsei (Ruthven), E. surinamensis (Daudin), and Elachistocleis sp. (Kenny 1969; Williams & Gudynas 1987; Kwet & Di-Bernardo 1998; Duellman 2005; Lynch 2006; Rossa-Feres & Nomura 2006; Vera Candioti 2006; Magalhães et al. 2012; Pereyra et al. 2013).